HUKUM MEMPELAJARI FILSAFAT DALAM ISLAM: TELAAH KITAB FASHL AL-MAQAL KARYA IBNU RUSYD - Restu Subekti, Fiqi; Awan Wibowo, Taufik; Rizky Shorfana, Muhammad (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
This research aims to undertake a critical analysis of the juridical status of studying philosophy in Islam, with particular emphasis on Ibn Rushd’s perspective as presented in the aforementioned treatise. The methodology employed is qualitative, based on a library-research approach. The primary source is the text of Fashl al-Maqāl itself, supplemented by secondary materials including books, articles, journal publications, and other pertinent documents. The findings of this investigation yield two principal conclusions. First, the study of philosophy is recommended and even incumbent upon those who satisfy two principal conditions: intellectual aptitude and moral integrity consistent with sharʿi (Islamic legal) notions of justice. Second, the prohibition of philosophical inquiry applies to those lacking sufficient rational capacity and ethical standing. Consequently, the wholesale rejection of philosophy is not only unfounded but may also impede the intellectual development intrinsic to the Islamic scholarly tradition.